PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Survei pada Pelanggan DGC Coffeeshop di Solo, Kutoarjo, Sragen) - Sunarso, Yufita Ernawati, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
This research aimed to find out the effect of product and customerqualities either directly or with customer satisfaction as mediating variable onthe customer loyalty of DGC Coffeeshop in Solo, Kutoarjo, and Sragensubsidiaries. The sample consisting of 108 customers was taken from July 7to 23, 2017. Technique of collecting data used was questionnaire throughvalidity and reliability tests. Technique of analyzing data used was pathanalysis with classical assumption test. Technique of collecting data usedwas questionnaire through validity and reliability tests. Techniques ofanalyzing data used were path and classical assumption tests. From theresult of validity test, the research instrument of product quality, customerquality, customer satisfaction and product loyalty was valid. The result ofreliability test was reliable. From classical assumption test, multicoloniearity,heteroskedasticity, autocorrelation and normality tests passed through thetest successfully. The result of analysis showed that product and servicequalities affected customer satisfaction. Product and service qualities did notaffect directly the customer loyalty. Customer loyalty affected significantly thecustomer loyalty. Customer satisfaction affected significantly the customerloyalty. Customer satisfaction mediated the effect of product and servicequalities on customer loyalty.Keywords: product quality, service quality, customer satisfaction, customerloyalty